2022
DOI: 10.3390/jpm12060923
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Metabolomic and Nutritional Profiles among Children with Autism Spectrum Disorder

Abstract: There have been promising results regarding the capability of statistical and machine-learning techniques to offer insight into unique metabolomic patterns observed in ASD. This work re-examines a comparative study contrasting metabolomic and nutrient measurements of children with ASD (n = 55) against their typically developing (TD) peers (n = 44) through a multivariate statistical lens. Hypothesis testing, receiver characteristic curve assessment, and correlation analysis were consistent with prior work and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 98 publications
(141 reference statements)
0
3
0
Order By: Relevance
“…The diet plays a significant role in shaping the metabolome, and the dietary patterns directly impact metabolic profiles in children with ASD. Studies on metabolomics have identified differences in nutrient intake and metabolism between individuals with ASD and typically developing individuals[ 223 , 224 ]. In individuals with ASD, amino acid metabolism, lipid metabolism, and energy metabolism alterations have been observed[ 225 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diet plays a significant role in shaping the metabolome, and the dietary patterns directly impact metabolic profiles in children with ASD. Studies on metabolomics have identified differences in nutrient intake and metabolism between individuals with ASD and typically developing individuals[ 223 , 224 ]. In individuals with ASD, amino acid metabolism, lipid metabolism, and energy metabolism alterations have been observed[ 225 ].…”
Section: Discussionmentioning
confidence: 99%
“…ASD involves many more comorbidities and underlying factors for which dietary intervention may be helpful, such as mitochondrial dysfunction [24], gastrointestinal issues, immune system dysregulation, seizures, and sleep disturbances, as well as psychological conditions including anxiety, depression and behavior problems [3]. Further abnormalities include oxidative stress [25] disordered methylation, sulfation, and transsulfuration [26], and disordered oxalate metabolism [27].…”
Section: Introductionmentioning
confidence: 99%
“…These processes might result in metabolic dysregulations that can be observed in cord blood, detectable through metabolomics prior to the manifestation of autistic traits in early childhood. Multiple cross-sectional metabolomics studies among pre-school children with an ASD diagnosis and typically developing children have been conducted and suggested that mitochondrial dysfunction, immune dysregulation, as well as altered amino acid, lipid, and neurotransmitter metabolism could be associated with ASD [6][7][8][9][10][11][12][13][14][15][16][17][18]. Only one previous study assessed the prospective associations of stored dried blood spot metabolites in a small group of 37 newborns that received an ASD diagnosis in childhood and in healthy controls.…”
Section: Introductionmentioning
confidence: 99%